The Role Of The Teacher In Character Education In Madrasah - Ayu Puranti (STIT Attaqwa, 2023)
We are aware that currently most of our students are experiencing a character crisis problem, where they are not controlled by the influence of developments in Science and Technology. However, we have great hope that with the role of Religious Education teachers these concerns will be answered. Therefore, Madrasah teachers must teach good character and are expected to carry out their duties seriously in accordance with the goals of education and learning, namely forming and creating a generation with noble character, responsibility and character. Character education that is instilled continuously and continuously, such as getting used to being polite, respecting and paying attention to others, being responsible, being honest and helping each other, is implemented in schools, so that students can become good examples for the next generation.